Astragaloside IV protects against oxidized low‐density lipoprotein‐induced injury in human umbilical vein endothelial cells via the histone deacetylase 9 (HDAC9)/NF‐κB axis. Issue 3 (2nd November 2022) - Chen, Decai; Du, Yan; Ye, Shouwan; Yu, Jinsong
Abstract: Background: Atherosclerosis is a main cause of multiple cardiovascular diseases, and cell damage of human umbilical vein endothelial cells (HUVECs) was reported to participate in the development of atherosclerosis. In this study, we aimed to study the action of Astragaloside IV (ASV) on AS development using in vitro AS cell model. Methods: MTT assay, EdU staining assay, and flow cytometry were utilized for detection of cell proliferation and apoptosis, respectively. The protein expression of histone deacetylase 9 (HDAC9), Bax, Bcl‐2, p‐P65, P65, p‐IκBα, and IκBα was gaged using western blot. The angiogenesis was evaluated by tube formation assay. The inflammatory response was evaluated by ELISA kits. SOD activity and MDA level were detected using the matched commercial kits. RT‐qPCR was used for HDAC9 mRNA expression measurement. Results: Oxidized low‐density lipoprotein (ox‐LDL) significantly repressed cell proliferation, angiogenesis, and enhanced apoptosis, inflammation, and oxidative stress in HUVECs. ASV addition could alleviate ox‐LDL‐caused cell damage in HUVECs. Moreover, HDAC9 was overexpressed in AS patients and AS cell model. Functionally, HDAC9 knockdown also exhibited the protective role in ox‐LDL‐treated HUVECs. In addition, ASV treatment protected against ox‐LDL‐induced damage in HUVECs via targeting HDAC9. ASV could inactivate the NF‐κB pathway via regulating HDAC9 in AS cell model. Conclusion: ASV exerted the protective effects on ox‐LDL‐induced damage in HUVECs through the HDAC9/NF‐κB axis.